2015
DOI: 10.1364/oe.23.010198
|View full text |Cite
|
Sign up to set email alerts
|

Classification of peacock feather reflectance using principal component analysis similarity factors from multispectral imaging data

Abstract: Iridescent structural colors in biology exhibit sophisticated spatially-varying reflectance properties that depend on both the illumination and viewing angles. The classification of such spectral and spatial information in iridescent structurally colored surfaces is important to elucidate the functional role of irregularity and to improve understanding of color pattern formation at different length scales. In this study, we propose a non-invasive method for the spectral classification of spatial reflectance pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 52 publications
(150 reference statements)
0
13
0
Order By: Relevance
“…Structural colour is based on the arrangement of organelles (eg, melanosomes) or cell shapes (eg, barbules). Peacock tail feathers look blue or green based on iridescent and light interference . Another good example is the blackness produced by the tight interwoven of barbules in paradise birds.…”
Section: Complex Feather Pigment Patterns Results From a Combination Omentioning
confidence: 99%
“…Structural colour is based on the arrangement of organelles (eg, melanosomes) or cell shapes (eg, barbules). Peacock tail feathers look blue or green based on iridescent and light interference . Another good example is the blackness produced by the tight interwoven of barbules in paradise birds.…”
Section: Complex Feather Pigment Patterns Results From a Combination Omentioning
confidence: 99%
“…However, when the melanosome-air-layer stack consists of only a few periods (as in regions 3-6), minor changes in the spacing of the rst layers can cause distinct modulations in the reectance spectra. 28,29 We found that the keratin cortex and the melanosome diameter in the rst lattice periods play a prominent role in adjusting the peak shape. Interestingly, the effect of these peak shape modulating parameters decreases when the number of melanosome layers increases.…”
Section: Discussionmentioning
confidence: 90%
“…1,4 Subsequent spectrophotometry on peacock tail, neck and shoulder feathers yielded a variety of single-and double-peaked reectance spectra, which were interpreted by various optical methods. [26][27][28][29][30] We recently studied the blue feathers of the peacock's neck and breast, applying spectrophotometry and imaging scatterometry. The measured spectra could be well explained with an effective-medium multilayer model.…”
Section: Introductionmentioning
confidence: 99%
“…In colour science, the LED synthesiser can be used as the light source for BRDF (bidirectional reflectance distribution) measurements with an imaging hemispherical scatterometer36, or with an imaging angular reflectometer37. If larger scenes need to be illuminated from several angles, the LEDs and output fibres can be stacked in vertical columns around a single grating, or several LED synthesisers can be operated in synchrony.…”
Section: Discussionmentioning
confidence: 99%